Farmers' organizations - the missing link - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
It is a proven fact - there is strength in numbers. Take a look at any successful economy and you will find that much of the driving force comes from group activity. From teachers' unions to women's co-operatives, people from all backgrounds find...